Creativity and Self-Discipline as Predictors of Academic Success in Geospatial Engineering Education - Widia Ramadona; Bambang Heriyadi; Lasyatta Syaifullah (Postgraduate, University of Mataram, 2024)
The Rapid development of geospatial technology and increasing industry demands for competent workforce necessitate a deeper understanding of factors influencing student academic success in geospatial engineering education. This research aims to examine the contribution of creativity and self-discipline to student learning outcomes in the Fundamentals of Geospatial Engineering course. Specifically, it analyzes: (1) the contribution of creativity to learning outcomes, (2) the contribution of self-discipline to learning outcomes, and (3) the simultaneous contribution of both factors to the learning outcomes of tenth-grade students in the Geomatics Engineering Program at SMK Negeri 1 Sarolangun. The results show that learning creativity and self-discipline have a significant joint influence on student learning outcomes. Specifically, learning creativity has a positive and significant effect, where every one-unit increase in creativity will increase learning outcomes by 0.311 units. Likewise, self-discipline also has a positive and significant effect, where every one-unit increase in discipline will increase learning outcomes by 0.184 units. Simultaneously, learning creativity and self-discipline contribute 73.5% to student learning outcomes. These findings emphasize the importance of considering psychological and socio-emotional aspects, such as creativity and self-discipline, in an effort to improve the quality of learning and academic success of students in geospatial engineering education. The results of this research can be utilized to develop more effective and comprehensive learning strategies in the context of vocational education, particularly in the field of geospatial engineering.